Odpowiedź:
zad 3,31
a)
y = (x + 2)(x - 7)
(x + 2)(x - 7) = 0
x + 2 = 0 ∨ x - 7 = 0
x = - 2 ∨ x = 7
b)
y = 3(2x - 8)x
3(2x - 8)x = 0
3x(2x - 8) = 0
3x = 0 ∨ 2x - 8 = 0
x = 0 ∨ 2x = 8
x = 0 ∨ x = 8/2 = 4
d)
y = (x - 8)(x√3 + √6)
(x -8)(x√3 + √6) = 0
x - 8 = 0 ∨ x√3 + √6 = 0
x = 8 ∨ x√3 = - √6
x = 8 ∨ x = - √6/√3 = - √(6/2) = - √2
c)
y = - 4(x + 5)
x + 5 = 0
x = - 5
e)
y = (2 - 2x)(x - 3)
(2 - 2x)(x - 3) = 0
2 - 2x = 0 ∨ x - 3 = 0
- 2x = - 2 ∨ x = 3
x = - 2/(- 2) = 1 ∨ x = 3
f)
y = 3(4 -x + √2)²
(4 - x + √2)² = 0
4 - x + √2 = 0
- x = - 4 - √2
x = 4 + √2